2010
DOI: 10.3324/haematol.2010.026989
|View full text |Cite
|
Sign up to set email alerts
|

Post-thrombotic syndrome in children: a systematic review of frequency of occurrence, validity of outcome measures, and prognostic factors

Abstract: BackgroundPost-thrombotic syndrome is a manifestation of chronic venous insufficiency following deep venous thrombosis. This systematic review was conducted to critically evaluate pediatric evidence on frequency of occurrence, validity of outcome measures, and prognostic indicators of post-thrombotic syndrome. Design and MethodsA comprehensive literature search of original reports revealed 19 eligible studies, totaling 977 patients with upper/lower extremity deep venous thrombosis. Calculated weighted mean fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
149
3
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(163 citation statements)
references
References 73 publications
4
149
3
7
Order By: Relevance
“…Use of recognized pediatric‐specific VTE and bleeding‐event classification criteria13 and of a pediatric PTS scoring system10, 37, 38 will also aid such comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of recognized pediatric‐specific VTE and bleeding‐event classification criteria13 and of a pediatric PTS scoring system10, 37, 38 will also aid such comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Further, although estimates of rates of PTS in children vary considerably,7, 9, 10, 11 it has been found to be associated with increased morbidity and cost 39. There have been far fewer studies on the natural history, treatment, and secondary prevention of VTE in children than in adults 1, 9, 40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of PTS in the pediatric population reported an overall frequency of 26% [95% Confidence Interval (CI): [23][24][25][26][27][28] and a frequency of 17% [95% CI: [14][15][16][17][18][19][20] among prospective studies (9), including both UE and LE venous territories.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review identified two outcome-assessment tools that are commonly used in pediatric patients: the Modified Villalta Scale and the Manco-Johnson Instrument (9).…”
Section: Introductionmentioning
confidence: 99%